Regulasi Perwakafan Di Indonesia Dalam Perspektif Statute Approach - Chasanah, Kama Mir’atul; Maksum, Ghufron (STAINI Press, 2022)
The potential of waqf in Indonesia, if managed properly, can be the most appropriate instrument to solve social problems, especially in dealing with poverty. Waqf regulation in Indonesia has experienced a long dynamic, starting from pre-independence, post-independence until now. This paper aims to explain waqf regulations in Indonesia from the perspective of the statute approach. This study is included in the category of library research with primary sources in the form of laws and government regulations relating to waqf, while secondary sources in the form of journals, books and others related to the theme of discussion. The data obtained were described and then analyzed. This paper finds that: 1) The emergence of various waqf regulations after Indonesia's independence is full of regulations that are able to balance between Islamic and positive laws that apply in Indonesia. 2) Regulation of waqf in Indonesia started from Law Number 5 of 1960 concerning Agrarian Principles, Presidential Instruction of the Republic of Indonesia Number 1 of 1991 concerning KHI, Law Number 41 of 2004, then Government Regulation Number 42 of 2006. 3) Law Number 41 of 2004, is a new breakthrough in the waqf management system in Indonesia to become productive waqf.